Model Penerapan Akad Transaksi Syariah Pada BUMDes Pengalangan Sejahtera Dalam Masyarakat Pluralisme - Fira Kartika Ningtyas; Rohmawati Kusumaningtias (Universitas PGRI Madiun, 2021)
This research aim to determine the implementation model of sharia transaction contracts based on Fatwan DSN MUI and SAK Syariah at BUMDes Pengalangan Sejahtera. This study explain the application of sharia transactions in a pluralistic society to find out the understanding and interest of the community become a customer of a village bank based on sharia principles. The method used in this research is descriptive qualitative method with secondary and primary data. Supporting data collection was carried out by field studies through interviews, observation and documentation. The results of this study indicate that the implementation of the contract on BUMDes transactions is not in accordance with the Fatwa of the MUI and SAK Syariah DSN, so the researchers provide results in the form of a sharia contract implementation model in accordance with the various types of financing products applied by village banks to BUMDes Pengalangan Sejahtera. In general, the non-conformity of SAK Syariah lies in the preparation of BUMDes financial statements where there is no difference between recognition, measurement, presentation and disclosure. Meanwhile, according to the MUI DSN Fatwa, the non-conformity lies in several applicable provisions.